Comunidade Quilombola Invernada dos Negros e sua relação com o meio natural: um olhar da História Ambiental (Revista de História Regional, 2020)
The Quilombola Community Invernada dos Negros, located in the municipalities of Campos Novos and Abdon Batista / SC was thus recognized by the Fundação Palmares in 2004. The community has its own characteristics, but resembles others in issues such as freedom and access to land through testament. In the Testament dated 1877, Matheus José de Souza e Oliveira and Pureza Emilia da Silva left the slaves one-third of the land on the São João farm, corresponding to about eight thousand hectares of land consisting of fields and bushes. The territory consisted of cultivated land and farming fields, mostly virgin forests. It was regularly undulating in the countryside and quite bumpy in the bushes. The space was used by the legionaries for the production and breeding of animals. This article aims to analyze the relationship established historically between the descendants of the Invernada dos Negro´s legatars, with the environment, from the 1970s. The methodology used to understand such relationships was from Social History, dialoguing with Environmental History. Changes in the community's environment and way of life were observed and analyzed through judicial sources and the anthropological report produced by the Núcleo de Estudos sobre Identidade e Relações Interétnicas (NUER) da Universidade Federal de Santa Catarina (UFSC). From the sources, it was found that changes in the natural environment changed the way residents related to the natural environment, as well as the cultural and social life of the community.